Expression of nestin in embryonic tissues and its effects on clinicopathological characteristics of patients with placenta previa. Issue 2 (24th October 2017) - Qiao, Yan‐Yan; Chu, Ping
Abstract: In this study, we examined expression of nestin in the spinal cord, lung, kidney, stomach, colon, and intestine tissues at different stages of embryos in patients with placenta previa. Fetuses of 75 patients with placenta previa were assigned to case group and 80 fetuses from healthy pregnant women with normal placenta who voluntarily terminated pregnancy to control group. Clinical data of pregnant women were collected at the time of admission. Blood from elbow vein was collected to determine expression of serum nestin. Tissues from spinal cord, lung, kidney, stomach, colon, and intestine in 3‐7 months fetuses of the two groups were extracted. Expression of nestin in tissues was detected by immunohistochemistry, Western blotting and RT‐qPCR. The mRNA expression of nestin in the case group was increased. Nestin expression was correlated with the gestational age, age of foetus, and type of placenta previa in patients with placenta previa. Positive nestin expression was detected in the spinal cord, lung, kidney, stomach, intestine, and colon tissues in normal and placenta previa embryo at Stage I. The positive cell density and nestin expression decreased at Stage II, and further decreased at Stage III. The case group had higher nestin mRNA and protein levels throughout human fetal development. Findings of this study suggested that, nestin, as a specific marker of neural precursor cells, was expressed in various tissues of the embryo in patients with placenta previa and nestin expression was lower with increased maturation of the embryo. Abstract : Findings of this study suggested that, nestin, as a specific marker of neural precursor cells, was expressed in various tissues of the embryo in patients with placenta previa and nestin expression was lower with increased maturation of the embryo.